Malay Wisdom in Adapting Between Tauhid and Customs in Islamic Shari'at - Muhammad Nurin; Haris Riadi; Febby Erika (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to examine Malay wisdom in harmonizing tauhid (Islamic monotheism) and customary practices within the framework of Islamic law (shari’ah). The main focus is to explore how Malay society integrates the values of tauhid into its customary system, resulting in a harmonious relationship between religion and culture. This research employs a qualitative approach with a library research method, utilizing Islamic literature, books, and scholarly journals from the last five years as primary sources. Data collection is conducted through documentation, while data analysis applies a descriptive-analytical method with normative-theological and cultural approaches. The findings reveal that Malay wisdom operates through mechanisms of selection, adaptation, and integration in aligning tauhid with customary practices. The principle “adat bersendi syara’, syara’ bersendi Kitabullah” serves as the fundamental basis to ensure that customs remain within the boundaries of Islamic teachings. The values of tauhid are manifested in various cultural practices, including rituals, symbolic expressions, and social ethics that reflect Islamic teachings. However, in the modern era, Malay wisdom faces challenges such as globalization and value shifts that may weaken this integration. Therefore, revitalization efforts through education, the role of religious scholars, and policy support are necessary to sustain Malay wisdom grounded in tauhid.